2009
DOI: 10.1080/10428190902803677
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formation and survival of CD4+CD25hiFoxp3+T-cells in chronic lymphocytic leukemia

Abstract: Recently, it has been described that patients with chronic lymphocytic leukemia (CLL) have increased numbers of regulatory T (T(reg)) cells. In the present study, we analysed the mechanism behind T(reg) cells expansion in CLL. Neither analysis of the T-cell receptor repertoire nor CD45 isoform expression of T(reg) cells from patients with CLL provided evidence for chronic (tumor) antigenic stimulation as a possible cause for T(reg) cells expansion in CLL. We found evidence however for increased formation of T(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 43 publications
1
86
2
Order By: Relevance
“…Indeed higher than normal numbers of T regulatory cells have been found in CLL patients. [36][37][38][39] We show here that T regulatory cells (CD4 We further demonstrated that TGFb was the major cytokine involved in suppression of T-cell proliferation ( Figure 5B) and, in agreement with functional studies, NLC showed higher levels of TGFb mRNA expression than did normal monocytes. However, since simultaneous addition of antibodies against TGFb and IL-10, and IDO inhibitors resulted in greater and more significant effects when CLL-monocytes were co-cultured with T cells, it is likely that multiple factors cooperate in immunosuppression.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed higher than normal numbers of T regulatory cells have been found in CLL patients. [36][37][38][39] We show here that T regulatory cells (CD4 We further demonstrated that TGFb was the major cytokine involved in suppression of T-cell proliferation ( Figure 5B) and, in agreement with functional studies, NLC showed higher levels of TGFb mRNA expression than did normal monocytes. However, since simultaneous addition of antibodies against TGFb and IL-10, and IDO inhibitors resulted in greater and more significant effects when CLL-monocytes were co-cultured with T cells, it is likely that multiple factors cooperate in immunosuppression.…”
Section: Discussionsupporting
confidence: 68%
“…15,28 This relative NK-cell anergy could be due to the ability of CLL cells and their microenvironment to produce cytokines, such as IL-10, which suppress the proliferation of antigen-specific Th1 cells and downregulate co-stimulatory molecules on antigen-presenting cells. [29][30][31] Importantly, NK-cell function was perfectly recovered following activation. This included the ability to produce large amounts of IFN-g after IL-12 and IL-18 activation, and effective cytolysis against major histocompatibility complex % NK ADCC class-I-defective K562 target cells after IL-2 activation.…”
Section: Discussionmentioning
confidence: 90%
“…As a result, CD70 expression is tightly regulated, and it is only transiently expressed on activated T and B cells, as well as on subsets of professional antigen-presenting dendritic cells (DC) and natural killer (NK) cells (11). In contrast to the very limited expression of CD70 in a normal healthy individual, constitutive expression of CD70 has been documented in cancer (17)(18)(19) and chronic viral diseases (14).…”
Section: Cells This Conversion Of Naive T Cells To Induced (I)tregs mentioning
confidence: 99%